2019
DOI: 10.4274/jtsm.galenos.2019.46855
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Dry Eye Disease with Depressive Symptom Scores and Insomnia

Abstract: Kuru göz hastalığı göz yaşı içeriğini ve oküler yüzeyi etkileyen bir hastalıktır. Kornea epitel defektinden kornea delinmesine uzanan çeşitli oküler bulgular bu hastalıkla ilişkilidir (1). Kuru göz hastalığı en sık görülen göz hastalıklarından biridir. Yapılan toplum temelli prevalans çalışmalarında oranlar farklılık göstermekte olup %5 ile %35 arasında değişmektedir (2). Hastalık kadın cinsiyet, yaşlılar ve Asya ırkına mensup bireylerde daha sık gözlenmektedir (3-5). Etyopatogenezinde; hormonal değişimler, si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…These ndings suggest a relationship between psychological symptoms and the burden of DED [18], indicating that anxiety and depression may improve with the relief of dryness. Moreover, the observed decrease in symptoms of anxiety and depression may be attributed to the improvement in sleep quality [45], which has been reported to be compromised in patients with DED [14,46]. Although we found statistically signi cant differences in DED screening tests, including Schirmer, TBUT and OSDI between pre-and post-treatment assesments, a signi cant correlation was observed between the improvement in psychological well-being, including QoL and symptoms of depression and anxiety, and the amelioration in the Schirmer test results exclusively.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…These ndings suggest a relationship between psychological symptoms and the burden of DED [18], indicating that anxiety and depression may improve with the relief of dryness. Moreover, the observed decrease in symptoms of anxiety and depression may be attributed to the improvement in sleep quality [45], which has been reported to be compromised in patients with DED [14,46]. Although we found statistically signi cant differences in DED screening tests, including Schirmer, TBUT and OSDI between pre-and post-treatment assesments, a signi cant correlation was observed between the improvement in psychological well-being, including QoL and symptoms of depression and anxiety, and the amelioration in the Schirmer test results exclusively.…”
Section: Discussionmentioning
confidence: 96%
“…Additionally, studies have revealed a higher prevalence of psychiatric disorders in patients with DED [10][11][12]. Among psychiatric diagnoses, anxiety and depressive disorders were the most frequently investigated, and ndings consistently indicated that individuals with DED exhibited elevated levels of anxiety and depressive symptoms compared to those without DED [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the severity of insomnia were encountered in the literature review (Ayyıldız & Ayyıldız, 2019;Beşirli, 2020;Şahiner & Hisar, 2018). However, although research has been conducted in groups such as university students and healthcare professionals on the problem of insomnia during the COVID 19 pandemic period, no research has been encountered on the severity of insomnia of academicians working in the field of health sciences during this period (Ataç et al, 2020;İlhan et al, 2020;Salcan & Sarıkaya, 2020;Scotta et al, 2020;).…”
Section: Introductionmentioning
confidence: 99%